Assessment of differential branch pulmonary blood flow: a comparative study of phase contrast magnetic resonance imaging and radionuclide lung perfusion imaging. Issue 7 (14th June 2006) - Sridharan, S; Derrick, G; Deanfield, J; Taylor, A M
Abstract : Objectives: To test whether magnetic resonance (MR) imaging can be used to assess differential lung blood flow as accurately as isotope lung perfusion studies in patients investigated for congenital heart disease. Methods and results: Radionuclide lung perfusion and MR imaging were performed in 12 children with suspected unilateral branch pulmonary artery stenosis (mean age 12.1 (5.9) years, range 3.1–17.2 years). A non-breath hold, fast gradient echo phase contrast MR sequence was used to measure flow in the pulmonary trunk and one pulmonary artery to calculate differential flow. Good agreement was shown between the two imaging methods by Bland-Altman analysis. There was excellent correlation between the radionuclide and MR phase contrast calculated total lung blood flow ( r  =  0.98, p < 0.0001). Conclusion: MR phase contrast is an accurate method for measuring differential total right and left lung blood flow. If MR imaging is performed to assess the branch pulmonary arteries, differential lung blood flow can be also measured, avoiding the need for an additional radionuclide lung perfusion scan and reducing the overall radiation burden to this group of patients.